Experience in Transoral Robotic Surgery in Pediatric Subjects: A Systematic Literature Review - Vianini, Matteo; Fiacchini, Giacomo; Benettini, Giacomo; Dallan, Iacopo; Bruschini, Luca (Frontiers in surgery, 2021)
Pediatric transoral robotic surgery (TORS) has improved from 2007 to 2020, widening its indications and feasibility. This article aims to systematically analyze the procedures performed from the first use until the current year, observing their evolution over time. A systematic literature review was performed using PubMed, Scopus, Web of Science, and Cochrane databases between March 1, 2000, and April 1, 2020. We selected studies that were written only in English and were performed in live human subjects. About 16 studies were found with a total of 73 subjects treated, among them 41 were men and 32 were women with an average age of 6.8 ± 4.99 years. There have been four (5.47%) conversions. Both functional and benign-malignant diseases have been treated in the series. Eleven (15.06%) pre-operative tracheostomy and zero post-operative tracheostomy were performed. The bleeding data was only reported in 9 studies and was <50 ml. Only one (1.36%) intra-operative complication and 10 (12.32%) postoperative complications were reported. We consider the TORS procedures in pediatric subjects safe, feasible and with good surgical outcomes up to the laryngeal region.